Political Info Channels for West Java Governor Election Policy Prospective - Slamet, Adiyana; Yadi Supriadi (Mediator: Jurnal Komunikasi, 2023)
This research intends to analyze the use of communication channels by the West Java Governor candidates in 2018 to convey prospective policy choice political information to the voter segmentation in 27 regencies or cities. This research uses a qualitative method with a case study approach. The results showed that the communication channels used by West Java Governor Candidates through social media to disseminate prospective policy choice political information to the millennial generation segmentation in urban areas and through Islamic Boarding Schools reach Kiai, students, and the public in rural areas. It shows the importance of utilizing communication channels through social media. The other hand also shows the importance of professional organization channels through Islamic Boarding Schools and interpersonal communication to approach Kiai as an opinion leader to gain voters in the election for West Java Governor. Thus, this research benefits gubernatorial candidates in choosing communication channels to provide political information that must adjust to geographical and demographic conditions and to voters about how to obtain political information to gain knowledge of the regional head candidates. This research is still relevant as a study to make a sample of policy in the next election in 2024.